2015
DOI: 10.1097/jto.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Mucins in Lung Cancer: Diagnostic, Prognostic, and Therapeutic Implications

Abstract: Aberrant expression of mucins is associated with cancer development and metastasis. An overexpression of few mucins contributes to oncogenesis by enhancing cancer cell growth and providing constitutive survival signals. This review focuses on the importance of mucins both in the normal bronchial epithelial cells and the malignant tumors of the lung and their contribution in the diagnosis and prognosis of lung cancer patients. During lung cancer progression, mucins either alone or through their interaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 71 publications
(98 reference statements)
5
111
0
Order By: Relevance
“…35 Mucins interact with various molecules and affect cell–cell interaction during cancer progression and metastasis. 68 MUC5AC is a high molecular weight secretory polymeric mucin, synthesized as a glycoprotein in a selective and cell-specific manner. 5,9 Multiple cysteine-rich domains in both N- and C-terminal regions of MUC5AC are responsible for its disulfide-mediated polymerization, which is critical for gel-forming properties.…”
Section: Inroductionmentioning
confidence: 99%
“…35 Mucins interact with various molecules and affect cell–cell interaction during cancer progression and metastasis. 68 MUC5AC is a high molecular weight secretory polymeric mucin, synthesized as a glycoprotein in a selective and cell-specific manner. 5,9 Multiple cysteine-rich domains in both N- and C-terminal regions of MUC5AC are responsible for its disulfide-mediated polymerization, which is critical for gel-forming properties.…”
Section: Inroductionmentioning
confidence: 99%
“…We therefore investigated the relationship between CA 19-9 IHC positivity and pathological findings in patients with stage I lung adenocarcinoma. We analyzed the presence of cancer invasive factors (vessel and pleural invasion) and mucin production, which were reportedly associated with highly malignant features such as shorter recurrence-free survival and OS in lung adenocarcinoma patients [24, 29, 36]. In our pathological analysis of clinical stage I patients, CA 19-9 positive lung adenocarcinoma had more histologically malignant features ( P  = 0.005) and shorter recurrence-free survival ( P  = 0.030) than CA 19-9 negative lung adenocarcinoma (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one preliminary study demonstrated a signifi cant correlation between nonmucinous BAC histology and EGFR expression [14]. Nevertheless, the relation of mucins with EGFR expression in lung cancer is not complete clarifi ed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Airway mucins are major components of the soluble layer and/or viscoelastic gel that comprise lung mucus in healthy airways and contribute to the mucociliary defense system that protects the lungs against pathogens and environmental toxins [6]. Particularly, increased hyperproduction of secretory mucins usually occurs in lung tumors [5,7]. Nevertheless, their cellular localization and variations along the respiratory tract or occurring in respiratory diseases have received little attention.…”
Section: Introductionmentioning
confidence: 99%